2021
DOI: 10.1007/s00586-021-06829-w
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for an effect of working from home on neck pain and neck disability among Swiss office workers: Short-term impact of COVID-19

Abstract: Purpose The aim of this study was to investigate the effect of working from home on neck pain (NP) among office workers during the COVID-19 pandemic. Methods Participants from two Swiss organisations, aged 18–65 years and working from home during the lockdown (n = 69) were included. Baseline data collected in January 2020 before the lockdown (office work) were compared with follow-up data in April 2020 during lockdown (working from home). The primary outc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 30 publications
5
33
0
1
Order By: Relevance
“…Early in the pandemic, media accounts described widespread complaints of musculoskeletal strain and symptoms when people switched from ergonomic office furniture to long hours on laptops on their sofas, beds, and kitchen counters (Wilser 2020). Some (Moretti et al 2020) but not all (Aegerter et al 2021) studies corroborated this finding. Another category of WFH-associated risk is psychosocial, due to blurred boundaries between work and home, concurrent home responsibilities (such as childcare), increased workload, and social isolation (Bouziri et al 2020;Ingusci et al 2021).…”
Section: Infection-safe Buildings?mentioning
confidence: 82%
“…Early in the pandemic, media accounts described widespread complaints of musculoskeletal strain and symptoms when people switched from ergonomic office furniture to long hours on laptops on their sofas, beds, and kitchen counters (Wilser 2020). Some (Moretti et al 2020) but not all (Aegerter et al 2021) studies corroborated this finding. Another category of WFH-associated risk is psychosocial, due to blurred boundaries between work and home, concurrent home responsibilities (such as childcare), increased workload, and social isolation (Bouziri et al 2020;Ingusci et al 2021).…”
Section: Infection-safe Buildings?mentioning
confidence: 82%
“…Physical health is also the mediating factor for the productivity effect of WFH, and musculoskeletal symptoms are often discussed as a problem with WFH. While Moretti et al [ 29 ] and Yoshimoto et al [ 30 ] document that workers suffer from musculoskeletal issues due to WFH during the pandemic (see also [ 31 ]), Aegerter et al [ 32 ] find the effect of WFH on neck pain and disability to be limited, and Seva, Tejero, and Fadrilan-Camacho [ 33 ] show that musculoskeletal symptoms had no significant effect on the productivity of telecommuters. In summary, although there has been a rapid accumulation of studies on WFH and productivity, the reported evidence is mixed, and we believe that additional evidence on when WFH is productivity-enhancing is needed.…”
Section: Introductionmentioning
confidence: 99%
“…A review of 12 studies highlights the health risks that arise from musculoskeletal complaints when the workplace design is inadequate in WFH ( Wütschert et al, in press ). A recent longitudinal study, however, did not find an increase in musculoskeletal pain in Swiss office workers who worked from home full time after the COVID-19 pandemic outbreak, although ergonomic conditions were worse at home ( Aegerter et al, 2021 ). Moreover, no decrease in presenteeism was observed ( Aegerter et al, 2021 ).…”
Section: Introductionmentioning
confidence: 98%
“…A recent longitudinal study, however, did not find an increase in musculoskeletal pain in Swiss office workers who worked from home full time after the COVID-19 pandemic outbreak, although ergonomic conditions were worse at home ( Aegerter et al, 2021 ). Moreover, no decrease in presenteeism was observed ( Aegerter et al, 2021 ). Another recent large longitudinal study from February 2020 to February 2021, which covered the COVID-19 and lockdown-related increase in WFH, also found an increase in indicators of health and wellbeing and a decrease in presenteeism ( Galliker et al, 2021a ).…”
Section: Introductionmentioning
confidence: 98%